2014
DOI: 10.1016/j.ebcr.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A case of rhabdomyolysis in which levetiracetam was suspected as the cause

Abstract: Several studies have reported rhabdomyolysis induced by various drugs but not by the antiepileptic drug levetiracetam. We present a case of suspected levetiracetam-induced rhabdomyolysis. A 29-year-old woman was hospitalized for generalized tonic–clonic seizure and given levetiracetam for the first time. One day after starting levetiracetam, she developed myalgia, particularly backache, and weakness in both lower limbs. Based on her clinical symptoms and blood test results indicating hyperCKemia, our diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 10 publications
1
25
0
5
Order By: Relevance
“…Rhabdomyolysis is not a well-documented or listed adverse effect on this drug's profile but rare case reports have implicated levetiracetam as a cause of rhabdomyolysis [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyolysis is not a well-documented or listed adverse effect on this drug's profile but rare case reports have implicated levetiracetam as a cause of rhabdomyolysis [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, few adult patients have been reported, but there have been no reports in children [4,5]. Akiyama et al [4] reported a 29-year-old woman with epilepsy in whom rhabdomyolysis was induced by LEV. The other case, a 19-year-old man, was described by Isaacson et al [5].…”
Section: Sirmentioning
confidence: 97%
“…L evetiracetam is a commonly used medication for the treatment of partial‐onset and primary generalized epilepsy due to its favorable pharmacokinetics, lack of drug interactions, and availability of bioequivalent oral and intravenous forms . Commonly reported adverse effects of levetiracetam are somnolence, asthenia, headache, and irritability …”
mentioning
confidence: 99%
“…There have been 4 reports of levetiracetam‐associated rhabdomyolysis . All occurred in the setting of epilepsy treatment and involved young patients aged 13 to 29 years, with resulting CK levels ranging from 986 to 29,136 U/L . Myalgia was reported in 2 patients and muscle weakness in 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation